Motivation Based Engineering Education-A Case Study at RK University - Patel, Chetankumar M.; Chauhan, Dipesh M. (Journal of Engineering Education Transformations, 2025)
Students who take admission in Engineering course are found to be capable, skilful and with infinite potentials. However, lack of motivation makes them dull. This paper discusses the cause of demotivation along with the symptoms. Solution to the problem is also discussed in form of a case study carried out at RK University.